2021
DOI: 10.21315/mjms2021.28.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Is the Mitochondrial Function of Keloid Fibroblasts Affected by Cytoglobin?

Abstract: Background: A keloid is a benign skin tumour characterised by excessive proliferation of fibroblasts, a process that requires a sufficient amount of energy. The energy needs are associated with adequate oxygen (O2) flow and well-functioning mitochondria. It is known that cytoglobin (CYGB) has a function in O2 distribution. The aim of the present study was to explore whether the inhibition of CYGB expression caused impaired mitochondrial function of keloid fibroblasts. Methods: An in vitro study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…( 16 ) Furthermore, it showed that inhibition of CYGB mRNA expression using siRNA tends to reduce the expressions of PGC1-α mRNA and protein, which are markers of mitochondrial biogenesis, and the activity of the SDH enzyme, which plays a role in the process of energy formation in the TCA cycle. ( 15 ) Inhibition of CYGB expression using siRNA tends to decrease mitochondrial function and biogenesis, which can interfere with the production of the energy needed to support the viability and proliferation of keloid fibroblasts. Our present study supports our previous studies regarding the effect of CYGB on the viability and proliferation of keloid fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…( 16 ) Furthermore, it showed that inhibition of CYGB mRNA expression using siRNA tends to reduce the expressions of PGC1-α mRNA and protein, which are markers of mitochondrial biogenesis, and the activity of the SDH enzyme, which plays a role in the process of energy formation in the TCA cycle. ( 15 ) Inhibition of CYGB expression using siRNA tends to decrease mitochondrial function and biogenesis, which can interfere with the production of the energy needed to support the viability and proliferation of keloid fibroblasts. Our present study supports our previous studies regarding the effect of CYGB on the viability and proliferation of keloid fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…( 14 ) Our previous study showed that inhibiting CYGB expression using siRNA reduces mitochondrial biogenesis in keloid fibroblasts, as shown by the lower expression levels of PGC1-mRNA and protein. ( 15 ) In addition, the inhibition of CYGB expression using siRNA tends to reduce the activity level of the enzyme succinate dehydrogenase (SDH), which plays a role in the energy formation process in the tricarboxylic acid (TCA) cycle. ( 15 ) Although inhibition of CYGB expression using siRNA tends to decrease mitochondrial biogenesis and SDH activity levels, its effect on keloid fibroblast proliferation is still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SDH comprises SDHA, SDHB, SDHC, SDHD, SDHAF1, SDHAF2 subunits [3], and exhibits tumor-suppressing effects [4]. A decreased SDH activity leads to the accumulation of succinate, thus triggering the stabilization of the hypoxia-inducible factor (HIF) through competitive inhibition of HIF prolyl hydroxylases [5]. A stabilized HIF triggers pseudo-hypoxia signaling, leading to angiogenesis, dysregulation of cell proliferation, and adhesion [6].…”
Section: Introductionmentioning
confidence: 99%